Antifouling potential of multi-walled carbon nanotubes-modified chlorinated rubber-based composites on the colonization dynamics of pioneer biofilm-forming eukaryotic microbes. (April 2020) - Sun, Yuan; Lang, Yanghe; Sun, Tiedong; Liu, Qianqian; Pan, Yusheng; Qi, Zheng; Ling, Na; Feng, Yajie; Yu, Miao; Ji, Yubin; Zhang, Zhizhou
Abstract: Chlorinated rubber (CR)-based materials available for artificial surfaces have important commercial and industrial applications. However, CR-based materials are susceptible to diverse biofouling. In this study, different amounts (i.e. 0.2 wt % and 2 wt %) of multi-walled carbon nanotubes (MWCNTs) were incorporated into the CR matrix (CF0 ), respectively, in order to prepare the MWCNTs-modified CR composites (MCRCs, CF1 and CF2 ) with improved antifouling (AF) properties. The CR-based coatings were characterized using the SEM technique and then examined in the natural seawater via long-term field exposure assays. The impact of MCRCs on the colonization dynamics of pioneer eukaryotic microbes (PEM) in the natural biofilms with regard to their diversity, abundance, distribution patterns and succession process was investigated using the single-stranded conformation polymorphisms (SSCP) technique. MCRCs demonstrated differential surface structure features and enhanced AF properties compared with the unfilled CR matrix. The diversity and abundance of the PEM on the MCRC surfaces were found to be lower than that of the CR matrix, particularly reduced on the CF2 surfaces (P < 0.05); while the dominant population of PEM on the MCRCs was significantly higher than that of the CR matrix (P < 0.05). This indicated the colonization of the PEM on MCRC surfaces was greatly perturbed by the incorporation of MWCNTs in the CR matrix, as well supported by the reduced Evenness index and the clustering patterns. It seems that MWCNTs incorporated in the CR matrix would result in differential surface structures, enhanced AF properties and reinforced perturbation effect on PEM, which would further impede the development of natural biofilms and conduce to the prevention of macrofouling formation. MCRCs would have potential applications in future coating industries for biofouling mitigation. Highlights: MWCNTs-modified chlorinated rubber-based composites (MCRCs) for anti-biofouling applications were prepared. The MCRCs have decent AF properties as determined in the field. MCRCs can reduce the diversity and abundance of pioneer eukaryotic microbes. MCRCs can impede the development of natural biofilms and prevent macrofouling. The possible mechanisms of MCRCs against biofouling were explored.